Respon Pertumbuhan Dan Produksi Tanaman Sawi (Brassica juncea L.) Terhadap Interval Waktu Pemberian POC Urin Kelinci - Linda Ernawati Lindongi; Amelia Sarungallo; Olina Yahuli; Inna M. Rumainum (Agrotek, 2023)
This study aims to determine the appropriate application time interval of rabbit urine POC to support optimal growth and production of mustard greens. This study used an experimental method designed using a completely randomized design (CRD) with 4 treatments, including W0 (control), W1 (treated with 60 ml/L rabbit urine every 1 week), W2 (treated with 60 ml of rabbit urine /L every 2 weeks), and W3 (treated with 60 ml/L rabbit urine fertilizer every 3 weeks). Variables observed in this study included growth variables consisting of plant height, number of leaves, leaf width, and leaf length at 1 – 6 WAP, as well as production variables in the form of wet stover weight per plant (grams) and plant consumption weight (grams) at 6 WAP. The data obtained were analyzed by ANOVA and if it had a significant effect then continued by the Tukey test at the 95% level of confidence. The results of the study showed that the time interval treatment for application of POC rabbit urine only had a significant effect on the variable number of leaves, leaf length, and leaf width at 6 WAP and plant consumption weight. The time interval application of 2 weeks (W2) rabbit urine POC tend to give better results than other time interval treatments in almost all observation variables.